2019
DOI: 10.1177/0883073819884169
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiologic Profile and Outcome of Children With Tubercular Meningitis in a Tertiary Care Hospital in Bangladesh

Abstract: Background: Children are most vulnerable to tubercular meningitis. Neuroimaging is an important initial investigation in tubercular meningitis. Objective: This study was done to describe the clinical profile, neuroimaging changes, and clinical outcome in children with tubercular meningitis. Methodology: This was an observational cohort study on children with tubercular meningitis, between January 2012 and June 2018. Tubercular meningitis was diagnosed on the basis of clinical criteria, cerebrospinal fluid anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(28 reference statements)
3
7
0
Order By: Relevance
“…Nearly, one-third (28.1%) were discharged with neurological sequelae and the remains (38.0%) were discharged with a normal outcomes. This is comparable to studies conducted in Indonesia (26.5%), 3 Bangladesh (33%), 6 and India 18 However, it is higher than that reported in many studies such as Uganda (8%), 10 Ethiopia (14.3%), 21 South Africa (13%), (11.1%), 4 , 34 and supported by systematic review and meta-analysis (19.3%). 5 This may be due to children presenting to the hospital at an advanced stage of the disease and complications of TBM such as seizures, raised intracranial pressure, brain herniation, and hydrocephalus.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Nearly, one-third (28.1%) were discharged with neurological sequelae and the remains (38.0%) were discharged with a normal outcomes. This is comparable to studies conducted in Indonesia (26.5%), 3 Bangladesh (33%), 6 and India 18 However, it is higher than that reported in many studies such as Uganda (8%), 10 Ethiopia (14.3%), 21 South Africa (13%), (11.1%), 4 , 34 and supported by systematic review and meta-analysis (19.3%). 5 This may be due to children presenting to the hospital at an advanced stage of the disease and complications of TBM such as seizures, raised intracranial pressure, brain herniation, and hydrocephalus.…”
Section: Discussionsupporting
confidence: 72%
“…The most common neurological sequelae were blindness, hearing loss, motor deficits, cranial nerve palsy, hydrocephalus, and mental retardation. 3 , 6 , 7 According to a hospital-based study in South Africa, TBM affects more than 10% of tuberculosis cases and about 8% and 50% had treatment outcomes of death and neurological disability among children, respectively. 8 , 10 The disease burden increases up to one-fifth of the cases with a mortality rate of 15% and neurological sequelae of 21%.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,17,21,23,26,30 This higher incidence of tuberculomas could be due to better imaging techniques or a changing pattern of tubercular meningitis. Fatima et al 27 has also showed tuberculoma in 50% cases. In the present study, tubercular meningitis associated tuberculomas were either solitary or multiple, involving the posterior parts of the brain, basal ganglia, and thalamus.…”
Section: Discussionmentioning
confidence: 90%
“…2,14,17,20,24 -26 Over the years, the percentage of patients presenting with altered sensorium has decreased markedly; an explanation could be increased awareness about the disease leading to an early diagnosis or fewer patients progressing to its severe form because of partial treatment with antibiotics with antitubercular effect prior to presentation. 19,21,27 Loss of appetite and weight loss, which are classical features of tuberculosis, were seen in very few patients. Isolated tuberculomas patients had seizures as the most common presenting complaint; other studies have also reported headache, vomiting, and fever with varying frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation